The American christian right’s response towards the Israel-Palestine Conflicts - Mohd Afandi Salleh,; Abdul Majid Hafiz Mohamed, (Penerbit UKM, 2012)
This article explores the critical response of the Christian Right towards the Israel-Palestine conflicts by examining two events: the 2002 Road Map Peace Plan and the Annapolis Conference. It seeks to examine the critical role of the Christian Right in American foreign policy during the George W. Bush administration, with particular regard to Israel and Palestine. It argues that the Christian Right has consistently demonstrated its earnest concern about American foreign policy towards Israel, particularly the present Israel-Palestine conflict resolution. However, the paper seeks to establish that, after 9/11, the Christian Right extended its support for Israel beyond its traditional theological partiality and that such support was offered under a banner of American national security and the War on Terror. However, the study also shows how mainstream evangelicals are often divided in their opinions on the issue of the Christian Right’s unequivocal support for Israel.